Comparison of three prognostic models for predicting cancer-specific survival among patients with gastrointestinal stromal tumors - Oweira, Hani; Schmidt, Jan; Mehrabi, Arianeb; Kulaksiz, Hasan; Schneider, Paul; Schöb, Othmar; Giryes, Anwar; Abdel-Rahman, Omar (Future oncology, 2018)
Aim: To evaluate the predictive value for cancer-specific survival of the models of the American Joint Committee on Cancer (AJCC) stage, NIH and Armed Forces Institute of Pathology (AFIP) among patients with gastrointestinal stromal tumors (GISTs). Methods: Surveillance, Epidemiology and End Results database (2010-2014) was accessed. Overall survival analysis and adjusted cancer-specific Cox regression hazard was calculated. Results: For gastric GISTs, concordance-index according to AJCC was 0.834; according to NIH was 0.833; according to AFIP was 0.836. Concordance-index for nongastric GISTs according to AJCC was 0.800, according to NIH was 0.801 and according to AFIP was 0.799. Conclusion: The performance of the three models is comparable with regards to cancer-specific survival prediction.
Gesehen am 11.03.2020